Analisis laporan keuangan untuk mengukur kinerja keuangan pada PT Kimia Farma Tbk Periode 2018-2022 - Yuliana, Mia Noor Aida; Choiriyah, Nanda Septiani; Endarwati (Journal of Economics, Business, Accounting and Management, 2023)
Assessment of the financial performance of a company can be done by analyzing the company's financial statements for a certain period. In order for financial reports to be meaningful to users or those with an interest in financial reports, it is necessary to carry out an analysis of financial statements. The purpose of this study was to find out the analysis of financial statements to measure financial performance at PT Kimia Farma Tbk for the 2018-2022 period. The analytical method used is descriptive analysis using measurements of liquidity, solvency, activity and profitability ratios. The type of data used in this study is quantitative data sourced from secondary data, namely documents from the IDX/Indonesian Stock Exchange (IDX). The results of the study show that based on the calculation of the liquidity ratio, the company's financial performance is said to be unfavorable, marked by a decline that causes the company to be unable to carry out or pay its current obligations. Based on the calculation of the solvency ratio, it produces data that the company has increased, which makes the company's condition very worrying because the company is unable to pay debts in a timely manner. Based on the calculation of the activity ratio, it can be concluded that the overall condition of the company is good because the activity ratio has not decreased so that the company has been able to maximize the capacity of the company's fixed assets. Meanwhile, based on the calculation of the profitability ratio, it is not good because it has not been able to generate large profits and has not been able to manage the company's investment.